1997
DOI: 10.1038/sj.leu.2400588
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin augments ex vivo expansion of human cord blood-derived hematopoietic progenitors in combination with stem cell factor and flt3 ligand

Abstract: We studied the effects of stem cell factor (SCF) and flt3 ligand versus-host disease (GVHD). 1,4,6 However, the number of pro- factor (SCF) in combination with various cytokines, including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 4 publications
4
45
0
Order By: Relevance
“…The latter cocktail has been shown to be particularly effective in maintaining and slightly expanding human HSCs in suspension cultures up to 7 days. [25][26][27] In order to compare the data presented here with our former results we performed our experiments in Dexter-type cultures.…”
Section: Experimental Designmentioning
confidence: 98%
“…The latter cocktail has been shown to be particularly effective in maintaining and slightly expanding human HSCs in suspension cultures up to 7 days. [25][26][27] In order to compare the data presented here with our former results we performed our experiments in Dexter-type cultures.…”
Section: Experimental Designmentioning
confidence: 98%
“…171099, Nunc, Naperville, IL, USA), as reported elsewhere. [20][21][22][23][24][25] One milliliter of culture contained 200 sorted cells, 1.2% of 1500 centipoise methylcellulose (MTC, Shinetsu Chemical, Tokyo, Japan), 30% FCS, 1% deionized fraction V bovine serum albumin (BSA, Sigma Chemical, St Louis, MO, USA), 5 × 10 −5 mol/l 2-mercaptoethanol (2-ME, Sigma), and various combinations of CSFs. Final concentrations of each CSF were as follows: IL-3, 10 ng/ml; GM-CSF, 10 ng/ml; G-CSF, 20 ng/ml; Epo, 2 U/ml; SCF, 20 ng/ml.…”
Section: Clonal Cell Culutrementioning
confidence: 99%
“…On day 14 of incubation, all colonies were scored under an inverted microscope according to their typical morphologic features, as reported elsewhere. [20][21][22][23][24][25] The types of colonies identified in situ were granulocyte (G), macrophage (M), granulocyte/macrophage (GM), erythroid burst (B), eosinophil (Eo) and erythrocyte-containing mixed (CFU-Mix) colonies.…”
Section: Clonal Cell Culutrementioning
confidence: 99%
See 1 more Smart Citation
“…22,25,[39][40][41] Numerous studies have shown that IL-3 has an important role in survival 42 and ex vivo expansion of primitive cells. 25,43 We chose to study culture conditions that would maintain the primitive state of stem cells yet maximize the proportion of CD34 + cells in S-phase in order to determine the optimal time for gene transfer by electroporation. Our goal was to maintain CD34 pluripotency and optimize the culture conditions for electroporation using enhanced green fluorescence protein (EGFP) as a reporter gene.…”
mentioning
confidence: 99%